A cross-culture study of entrepreneurial intention: The moderating role of national culture - Ali, Muazam; Omar, Siti Sarah; Ali, Murtaza; Ahmad, Idayuwati; Yen, Wendy Teoh Ming (2023)
Abstract: The effects of entrepreneurship are many and multifaceted; they include the creation of new employment possibilities, the effective and efficient use of national resources and a positive improvement in the general well-being of the country residence. Various studies conducted on the Entrepreneurial Intention (EI); however, student EI are very fascinating and still demanding. Moreover, entrepreneurial cross-culture studies provide broad understanding about the EI internationally. Hence, this study is conducted on the EI of the university students in Pakistan and Malaysia. Its major goal is to pinpoint the factors that influence the EI of the university students of the emerging and developing countries. A quantitative research method is used for the data analysis. The data were collected from the public sector universities of Pakistan and Malaysia. A total number of 328 questionnaires were used for the data analysis. The hypothesis testing and empirical analysis are performed by the Smart PLS-SEM version 4.0. The findings of the research reveal that TPB equally affected the EI of the university students of Pakistan and Malaysia with the exception of subjective norms variable, which had a negative effect on Malaysian students. Moreover, the culture variable did not moderate the relationship between TPB and EI of the Pakistani students, although it is partially moderate the relationship of TPB and EI of the Malaysian university students. As a result, the research findings are crucial for policymakers in emerging and developing countries to comprehend and promote entrepreneurship both locally and internationally.